The Merdeka Curriculum and P5: A Review of Teachers' Understanding and Students' Experiences - Mellyzar, Mellyzar; Rochintaniawati, Diana; Riandi, Riandi; Fakhrah, Fakhrah; Virijai, Febrian (Universitas Galuh, 2025)
This study aims to analyze teachers' understanding of the Merdeka Curriculum and P5 and to identify the challenges, strategies, and impacts of implementing Project Strengthening Pancasila Student Profile (P5) on the development of students' character and skills using a qualitative approach. The research was conducted at a public high school in North Aceh Regency. The research subjects consisted of 13 teachers, 17 students, and the curriculum coordinator. The instruments used included interview guidelines and questionnaires for both teachers and students. Data collection techniques involved in-depth interviews and distribution of questionnaires. The primary data sources for this study include data obtained through in-depth interviews with teachers, students, and the curriculum coordinator, as well as the completed questionnaires from teachers and students. The questionnaires were designed to explore their perspectives, understanding, and experiences regarding the Merdeka Curriculum and the implementation of P5. This data provides a comprehensive overview of curriculum implementation as well as the obstacles and strategies applied by the school. The analysis of teachers' understanding of the Merdeka Curriculum shows that teachers grasp the basic concepts of the curriculum, although many face challenges in designing project-based learning. Obstacles such as diverse student interests and limited resources hinder the curriculum's implementation. The implementation of P5 has a positive impact on students' skills; however, its integration with lessons needs to be improved.